To convert the left-hand side of the equation \( x^2 - 8x + c = 13 \) into a perfect square trinomial, we need to determine the value of \( c \) that completes the square.
A quadratic expression of the form \( x^2 - bx \) can be written as a perfect square by using the formula:
\[ \left( \frac{b}{2} \right)^2 \]
In this case, \( b = 8 \). Now we calculate \( \left( \frac{8}{2} \right)^2 \):
\[ \frac{8}{2} = 4 \] \[ 4^2 = 16 \]
So, the value of \( c \) that makes \( x^2 - 8x + c \) a perfect square trinomial is \( 16 \).
Thus, the answer is:
\[ \boxed{16} \]